2016
DOI: 10.3382/ps/pev437
|View full text |Cite
|
Sign up to set email alerts
|

Temperature effect on proliferation and differentiation of satellite cells from turkeys with different growth rates

Abstract: Poultry selected for growth have an inefficient thermoregulatory system and are more sensitive to temperature extremes. Satellite cells are precursors to skeletal muscle and mediate all posthatch muscle growth. Their physiological functions are affected by temperature. The objective of the current study was to determine how temperature affects satellite cells isolated from the pectoralis major (p. major) muscle (breast muscle) of turkeys selected for increased 16 wk body weight (F line) in comparison to a rand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
53
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(61 citation statements)
references
References 62 publications
6
53
1
1
Order By: Relevance
“…In the heat-treated cells (43°C), MYOG was slightly downregulated (Log 2 FC = −1.11 and −1.06). This result is counter to a previous study using the same dissociated cell culture system that found increased MYOG expression, as measured by qPCR, in cells incubated at temperatures above 38°C (Clark et al, 2016a ). However, expression of MYOG in that study was conducted after 72 h of differentiation as opposed to 48 h as in the present study.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…In the heat-treated cells (43°C), MYOG was slightly downregulated (Log 2 FC = −1.11 and −1.06). This result is counter to a previous study using the same dissociated cell culture system that found increased MYOG expression, as measured by qPCR, in cells incubated at temperatures above 38°C (Clark et al, 2016a ). However, expression of MYOG in that study was conducted after 72 h of differentiation as opposed to 48 h as in the present study.…”
Section: Discussioncontrasting
confidence: 99%
“…However, expression of MYOG in that study was conducted after 72 h of differentiation as opposed to 48 h as in the present study. Satellite cells from both the RBC2 and F lines differentiate faster and produce larger myotubes at higher temperatures with slower growth at lower temperatures (Clark et al, 2016a ). This is consistent with the RNAseq results in that many muscle-associated genes were among the genes with the greatest down regulation in cold-treated cells (33°C).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Temperature can alter satellite cell proliferation, differentiation and ultimately cell fate [57–60], which can impact skeletal muscle growth and meat quality [58, 61]. Immature poults have an inefficient thermoregulatory system and are sensitive to extreme temperatures.…”
Section: Discussionmentioning
confidence: 99%
“…Detailed studies on cultured SCs from broilers (Harding et al, 2015(Harding et al, , 2016 and turkeys (Clark et al, 2016(Clark et al, , 2017 revealed that the pectoralis muscle, in particular, is highly sensitive to temperature changes. Yet, a decline in SCs did not result from increased apoptosis in either cultured cells (Harding et al, 2015) or the treated chicks (Patael et al, 2019).…”
Section: Negative Effects Of Thermal Stress On Sc Myogenesis In Posthmentioning
confidence: 99%